DEVELOPING OF CHILDRENS PARK PROGRAM ‘SITTI KHADIJAH’ IN ENREKANG DISTRICT - Haslinda Haslinda; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
Early childhood is a phase of human life that determines development. child development is supported by how the fulfillment of needs and in what way the fulfillment of these needs is done. For working parents, efforts to meet the needs of children are not carried out optimally. For this reason, there are alternatives for parents or working mothers so that they can continue to provide the rights of children and as an effort to avoid neglect by children. Childcare is a solution for those who have a career. Social service institutions in the field of child welfare are the role of temporary parents for children. The type of service is based on time, one of which is full day care, where children are kept for a full day at the TPA until parents or mothers finish work. This study aims to describe the implementation of full day care in one of the landfills in Bandung Regency. How is the implementation of full day care in terms of care / care programs, education, nutrition and health, human resources, and obstacles. The subject of this research is the Child Care Institute Subjects taken by purposive sampling technique or sample aims because it is expected to obtain informants who know about the research object. The method of this research is descriptive qualitative research. Data analysis used is data analysis done using data reduction, data presentation, and verification as well as triangulation. The results of the analysis with the literature study show that the implementation of the full day system must be based on the technical guidelines for implementing day care parks . Where all programs and activities are based on the fulfillment of children's rights and interests of children and on consideration of needs in the development phase.